Rare earth Dy < 3 + > doped X-ray induced red discoloration luminescent phosphate glass as well as preparation method and application thereof

The red color-discolored luminescent phosphate glass is induced by rare earth Dy3+ doped X-rays, and the photochromic and luminescence intensity changes are achieved by using X-ray irradiation, solving the problem of limited optical storage capacity, realizing high-density information storage and lossless reading, and the material has good stability in complex environments.

CN120271227APending Publication Date: 2025-07-08KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510394597.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

Traditional optical storage media are limited by grating diffraction limits, so they cannot improve storage capacity, and material performance is prone to decline during information reading.

Method used

Rare earth Dy3+ doped X-rays are used to induce red discoloration luminescent phosphate glass, and photodiscoloration is induced by X-ray irradiation, combined with changes in luminescence intensity to achieve information storage and lossless reading, optimize glass components and preparation processes to improve mechanical strength and stability.

Benefits of technology

Break through the grating diffraction limit, realize high-density information storage, ensure long-term stability and repeatability of information reading, and maintain high accuracy and reliability in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120271227A_ABST
    Figure CN120271227A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of glass preparation, and particularly relates to rare earth Dy < 3 + > doped X-ray induced red discoloration luminescent phosphate glass as well as a preparation method and application thereof, and the rare earth Dy < 3 + > doped X-ray induced red discoloration luminescent phosphate glass comprises the following raw materials in molar percentage: 60-66% of NH4H2PO4, 14-19% of K2CO3, 10-14% of BaCO3, 4-9% of Al2O3 and 0.2% of Dy2O3. The prepared luminescent glass transparent medium shows excellent red photochromism and radiation luminescence characteristics after irradiation, the luminescent intensity of the glass is gradually increased along with the increase of the X-ray irradiation dose, in addition, optical information can be written in the glass by adopting a projection mode, and the luminous intensity of the glass is greatly improved. Therefore, the photochromic luminescent glass induced by X-ray irradiation is expected to realize high-capacity and high-precision optical information storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of glass preparation, and particularly relates to a rare earth Dy 3+ -doped X-ray induced red color-changing luminescent phosphate glass and its preparation method and application. Background Art

[0002] With the rapid development of society and the advent of the big data era, there is an urgent need to develop large-capacity storage media. In information storage, cold storage accounts for 80% of the information market, which indicates the urgent need to develop new and large-capacity optical storage media. However, the storage capacity of traditional optical storage media is limited by the grating diffraction limit. Therefore, researchers have proposed multi-wavelength optical storage, holographic storage, super-resolution optical storage, etc. However, the high cost of equipment and complex operations limit the practical application of these technologies. To solve the problem of the grating diffraction limit, the inventor proposes to write optical information in glass by X-rays. Since X-rays have a shorter wavelength (0.001 - 10 nm) and stronger penetrability, storing information by X-rays is expected to break through the grating diffraction limit and achieve high-capacity information storage.

[0003] Chinese patent document CN201010022968.6 discloses a rare earth-doped luminescent glass and its preparation method; using rare earth ions Dy 3+ and Eu 3+ as the main components, doping them singly or co-dopingly in a phosphate glass matrix. Under the excitation of 360 nm ultraviolet light, the rare earth ions can emit their respective characteristic lights, and there is an energy transfer from Dy 3+ to Eu 3+ . However, this patent only mentions the luminescent properties between luminescent ions. The present patent for the first time discloses that the glass can achieve X-ray-induced photochromism, establishes an optical connection between color change and luminescence, realizes the regulation of luminescent properties based on color change, and applies it to multi-modal optical information storage.

[0004] Storing information by X-ray irradiation-induced photochromism can achieve a high information storage capacity. However, the lossless reading of information is crucial for optical storage media. To solve this problem, the present invention regulates the luminescence intensity through color change by doping with rare earths having excellent luminescence efficiency. Therefore, the color change based on transmittance and the change in luminescence intensity can achieve lossless reading of information. The present invention proposes a rare earth Dy 3+ -doped X-ray induced red color-changing luminescent phosphate glass is expected to break through the existing optical storage technology and open up a new generation of optical information storage devices. Summary of the Invention

[0005] The purpose of the present invention is to provide a rare earth Dy 3+Doped X-ray induced red color-changing luminescent phosphate glass, its preparation method and application. The luminescent glass transparent medium prepared in the present invention exhibits excellent red photochromic and radioluminescent properties after irradiation. As the X-ray irradiation dose increases, the luminescence intensity of the glass gradually increases. In addition, optical information can be written into the glass by projection. Therefore, this X-ray irradiation-induced photochromic luminescent glass is expected to achieve a high-capacity and high-precision optical information storage.

[0006] To achieve the above technical purposes and reach the above technical effects, the present invention is realized through the following technical solutions:

[0007] A rare earth Dy 3+ Doped X-ray induced red color-changing luminescent phosphate glass, comprising raw materials in the following molar percentages: NH4H2PO4: 60 - 66%, K2CO3: 14 - 19%, BaCO3: 10 - 14%, Al2O3: 4 - 9%, Dy2O3: 0.2%.

[0008] Further, it comprises raw materials in the following molar percentages: NH4H2PO4: 60 - 66%, K2CO3: 14 - 19%, BaCO3: 10 - 14%, Al2O3: 4 - 9%, Dy2O3: 0.5%.

[0009] Further, it comprises raw materials in the following molar percentages: NH4H2PO4: 60 - 66%, K2CO3: 14 - 19%, BaCO3: 10 - 14%, Al2O3: 4 - 9%, Dy2O3: 1%.

[0010] On the other hand, the present invention provides a preparation method of the above glass, comprising the following steps:

[0011] S1: Weigh and mix the above raw materials evenly, sinter at 1150 °C for 1.5 h under an air atmosphere, then pour the glass liquid onto a brass mold preheated to 370 °C, and then cool to room temperature;

[0012] S2: Heat the glass prepared in S1 to 380 °C and keep it warm for 8 hours to remove the residual stress in the glass, thereby improving the mechanical strength of the glass;

[0013] S3: Grind and polish the glass obtained in S2 to prepare a glass with X-ray irradiation-induced photochromic luminescence;

[0014] S4: Irradiate the glass prepared in S3 with X-rays.

[0015] Further, the rare earth Dy irradiated by X-rays 3+The doped X-ray induced red color-changing luminescent phosphate glass exhibits both photochromic and radioluminescent properties simultaneously. The transmission spectrum of the glass was measured using a spectrophotometer (U-4100) equipped with an integrating sphere.

[0016] On the other hand, the present invention proposes the application of the above-mentioned glass in photochromic information storage induced by X-ray irradiation.

[0017] Advantages of the present invention:

[0018] The present invention utilizes the ultra-short wavelength characteristics of X-rays, breaking through the limitation of the grating diffraction limit in traditional optical storage technology and achieving sub-nanometer high-density information storage. The wavelength of X-rays is much smaller than that of visible light, enabling it to achieve higher spatial resolution and storage density. In Example 3, an information pattern ( Figure 4 ) was successfully written on the glass surface by projection, demonstrating the feasibility of high-precision information writing by X-rays at the nanoscale. X-ray irradiation induces the generation of color center defects in the glass matrix, specifically manifested as enhanced absorption in the visible light region ( Figure 2 ), resulting in the glass showing red color change. The stability of this process is closely related to the introduction of Al2O3 in the glass composition: Al 3+ forms the [AlO4] structure with the phosphate network, acting as an electron trap to capture the carriers excited by X-rays and forming stable defect centers, thereby achieving long-term stable storage of information. In addition, the strong penetrability of X-rays enables the formation of three-dimensional information storage units inside the glass, providing a material basis for the future development of multi-layer or volume holographic storage technologies. It not only solves the key problem of limited storage density in traditional optical storage technology but also provides a practical solution for the high-capacity storage requirements in the big data era.

[0019] This technical solution realizes non-destructive reading of information based on the synergistic effect of photochromism and luminescence intensity change by introducing rare earth Dy 3+ ions, ensuring the long-term stability and repeatability of the stored information. In Example 1, as the doping concentration of Dy 3+ increases, the luminescence intensity increases significantly, demonstrating that the luminescence characteristics of Dy 3+ can be precisely regulated by the doping concentration. After X-ray irradiation, there is an energy competition between the formation of color center defects and the Dy 3+ luminescence centers in the glass: the color centers absorb part of the excitation energy, resulting in a decrease in the Dy 3+ luminescence intensity with the increase of the irradiation dose ( Figure 3)。It provides a non-destructive detection method based on the change in luminescence intensity for information reading. Information can be read by measuring the change in luminescence intensity without destroying the color center structure (i.e., without erasing the stored information), solving the key problem of performance degradation of traditional photochromic materials during repeated reading processes. This dual-mode response mechanism not only improves the accuracy and reliability of information reading but also provides technical guarantees for the long-term application of optical storage materials.

[0020] Through optimizing the glass composition and preparation process, this technical solution significantly improves the mechanical strength, thermal stability, and chemical stability of the material, enabling it to meet the long-term use requirements under complex environments. The introduction of BaCO3 in the raw materials as a high-field-strength ion increases the interaction efficiency between the glass density and X-rays; the addition of K2CO3 reduces the melting temperature of the glass, ensuring the uniform doping of Dy 3+ ions; the introduction of Al2O3 strengthens the glass network structure and improves the chemical stability of the material. In the preparation process, through the annealing treatment at 380 °C for 8 hours, the residual stress in the glass is effectively eliminated, significantly improving the mechanical strength of the material. Experimental results confirm that the annealed glass does not show cracking or deformation during subsequent polishing and irradiation treatments, indicating that its structural stability meets the actual application requirements. In addition, the high chemical stability of the phosphate matrix itself, combined with the strengthening effect of Al2O3 on the network structure, enables the color center defects in the glass to remain stable during long-term storage.

[0021] Of course, it is not necessary for any product implementing the present invention to simultaneously achieve all the above-mentioned advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the following will briefly introduce the drawings required for describing the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.

[0023] Figure 1 is the irradiation emission spectrum with different concentrations of Dy2O3 doping in Embodiment 1 of the present invention;

[0024] Figure 2 is the transmission spectrum of the glass doped with 0.5% Dy2O3 before and after X-ray irradiation in Embodiment 2 of the present invention, as well as the corresponding glass photos;

[0025] Figure 3 is the emission spectrum of the glass doped with 0.5% Dy2O3 under different doses of X-ray irradiation in Embodiment 2 of the present invention;

[0026] Figure 4In Example 3 of the present invention, after doping 0.5% Dy2O3, optical information was written by X-ray irradiation in a projection manner. Detailed implementation manners

[0027] The following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the scope of protection of the present invention.

[0028] Example 1

[0029] A preparation method of a rare earth Dy 3+ doped X-ray induced red color-changing luminescent phosphate glass, comprising the following steps:

[0030] S1: Weigh and mix the raw materials in a molar ratio of NH4H2PO4: 60%, K2CO3: 19%, BaCO3: 14%, Al2O3: 6.8%, 6.5%, 6%; Dy2O3: 0.2%, 0.5%, 1% evenly. Under the condition of an air atmosphere, sinter at 1150 °C for 1.5 h, then pour the glass liquid onto a brass mold preheated to 370 °C in advance, and then cool to room temperature;

[0031] S2: The glass prepared in S1 has a large amount of thermal stress. Heat this glass to 380 °C and keep it warm for 8 hours to remove the residual stress in the glass, thereby improving the mechanical strength of the glass;

[0032] S3: Grind and polish the glass obtained in S2 to prepare a glass with X-ray irradiation-induced photochromic luminescence;

[0033] S4: Perform luminescence characterization on the glass prepared in S3.

[0034] In this Example 1, by doping (0.2 - 1)% Dy2O3 in the glass, Figure 1 it can be seen that the glass emits yellow light, and the spectrum shows the typical photoluminescence spectrum of Dy3+, and it increases with the increase of the doping concentration.

[0035] Example 2

[0036] A preparation method of a rare earth Dy 3+ doped X-ray induced red color-changing luminescent phosphate glass, comprising the following steps:

[0037] S1: Weigh and mix the raw materials according to the molar ratio of NH4H2PO4: 66%, K2CO3: 14%, BaCO3: 10.5%, Al2O3: 9%, Dy2O3: 0.5%. Under the condition of air atmosphere, sinter at 1150 °C for 1.5 h. Then pour the glass liquid onto a brass mold preheated to 370 °C in advance, and then cool to room temperature;

[0038] S2: The glass prepared in S1 has a large amount of thermal stress. Pass the glass through 380 °C and keep it warm for 8 hours to remove the residual stress in the glass, thereby improving the mechanical strength of the glass;

[0039] S3: Grind and polish the glass obtained in S2 to prepare a glass with X-ray irradiation-induced photochromic luminescence;

[0040] S4: Irradiate the glass prepared in S3 with X-rays at different doses.

[0041] In this Example 2, the doping concentration of the glass is 0.5% Dy2O3. As Figure 2 shown, the glass exhibits obvious photochromic properties after X-ray irradiation, and its transmission spectrum also shows obvious absorption. In addition, the transparent glass medium exhibits obvious irradiation luminescence phenomenon during X-ray irradiation. As Figure 3 shown, the luminescence intensity of the glass increases with the increase of the X-ray irradiation dose, demonstrating that this glass also has great application prospects in the fields of X-ray dose detection, etc.

[0042] Example 3

[0043] A preparation method of a rare earth Dy 3+ -doped X-ray-induced red color-changing luminescent phosphate glass includes the following steps:

[0044] S1: Weigh and mix the raw materials according to the molar ratio of NH4H2PO4: 66%, K2CO3: 19%, BaCO3: 10%, Al2O3: 4%, Dy2O3: 1%. Under the condition of air atmosphere, sinter at 1150 °C for 1.5 h. Then pour the glass liquid onto a brass mold preheated to 370 °C in advance, and then cool to room temperature;

[0045] S2: The glass prepared in S1 has a large amount of thermal stress. Pass the glass through 380 °C and keep it warm for 8 hours to remove the residual stress in the glass, thereby improving the mechanical strength of the glass;

[0046] S3: Grind and polish the glass obtained in S2 to prepare a glass with X-ray irradiation-induced photochromic luminescence;

[0047] S4: Irradiate the glass prepared in S3 with X-rays at different doses.

[0048] S5: Write optical information on the glass surface by X-ray irradiation in a projection manner.

[0049] In this Example 3, for the glass doped with 0.5% Dy2O3, an information pattern was written on the glass surface in a projection manner, as Figure 4 shown. The contour of the pattern was clearly observed. Therefore, if a nanoscale mask is used and taking advantage of the penetrability of X-rays, it is expected to achieve a nanoscale high-capacity information storage, such as on a chip with a size of a few nanometers.

[0050] In summary, the rare earth Dy 3+ -doped X-ray-induced red color-changing luminescent phosphate glass of the present invention can be applied to high-capacity information storage, solving the key problem in the existing cold storage technology that optical storage is limited by the grating diffraction limit and cannot improve the information storage capacity. It has more advantages compared with the existing optical storage technology. Taking advantage of the characteristics of short wavelength and high penetrability of X-rays, it is expected to achieve a sub-nanoscale information storage.

[0051] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all details in detail, nor limit the invention to the specific embodiments described. Obviously, many modifications and variations can be made according to the content of this specification. These embodiments are selected and specifically described in this specification to better explain the principle and practical application of the present invention, so that those skilled in the art can understand and utilize the present invention well. The present invention is only limited by the claims and their full scope and equivalents.

Claims

1. A rare earth Dy 3+ doped X-ray induced red color-changing luminescent phosphate glass, characterized in that, It comprises raw materials in the following molar percentages: NH4H2PO4: 60 - 66%, K2CO3: 14 - 19%, BaCO3: 10 - 14%, Al2O3: 4 - 9%, Dy2O3: 0.2%.

2. Rare earth Dy as described in claim 1 3+ doped X-ray induced red color-changing luminescent phosphate glass, characterized in that: It comprises raw materials in the following molar percentages: NH4H2PO4: 60 - 66%, K2CO3: 14 - 19%, BaCO3: 10 - 14%, Al2O3: 4 - 9%, Dy2O3: 0.5%.

3. Rare earth Dy as described in claim 1 3+ doped X-ray induced red color-changing luminescent phosphate glass, characterized in that: It comprises raw materials in the following molar percentages: NH4H2PO4: 60 - 66%, K2CO3: 14 - 19%, BaCO3: 10 - 14%, Al2O3: 4 - 9%, Dy2O3: 1%.

4. The preparation method of the glass according to any one of claims 1-3, characterized in that: It comprises the following steps: S1: Weigh and mix the above raw materials evenly, sinter at 1150°C for 1.5 h under the condition of air atmosphere, then pour the glass liquid onto a brass mold preheated to 370°C in advance, and then cool to room temperature; S2: Heat the glass prepared in S1 to 380°C and keep it warm for 8 hours to remove the residual stress in the glass, thereby improving the mechanical strength of the glass; S3: Grind and polish the glass obtained in S2 to prepare a glass with X-ray irradiation-induced photochromic luminescence.

5. Use of the glass according to any one of claims 1 - 3 in photochromic storage of information induced by X-ray irradiation.

Citation Information

Patent Citations

  • Rare earth doped luminescent glass and preparation method thereof

    CN101759362A